2020
DOI: 10.1002/2050-7038.12610
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics and control of microgrids as a resiliency source

Abstract: Microgrids can be operated in a utility‐connected mode or an islanded mode in separation with the transmission or distribution system. As major disasters occur, intentional islanding of a microgrid is a possible solution to serve critical loads, within or outside the microgrids, until the utility service is restored. Through a field test, the technical feasibility to utilize microgrids as a resiliency resource is evaluated. Waveforms of the system dynamics are recorded, and the acquired data and measurements a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…where, dynamic real and reactive power control inputs and outputs are (p and q) and (u α and u β ), respectively. Since both the control inputs in (17) are coupled in P and Q states, by using voltage modulation theory [34], the dynamics of ( 17) can be simplified as (18) to define new voltage modulated control inputs:…”
Section: Dpc and Pvmt-based Pv-vsi Modellingmentioning
confidence: 99%
See 1 more Smart Citation
“…where, dynamic real and reactive power control inputs and outputs are (p and q) and (u α and u β ), respectively. Since both the control inputs in (17) are coupled in P and Q states, by using voltage modulation theory [34], the dynamics of ( 17) can be simplified as (18) to define new voltage modulated control inputs:…”
Section: Dpc and Pvmt-based Pv-vsi Modellingmentioning
confidence: 99%
“…Since in the aforementioned methods, Park's transformation has been used during abc to dq transformation, there is a need for phase angle extraction from grid voltages to ensure dq axes currents and grid voltages are in phase with each other [18]. Phaselocked loop (PLL) systems are commonly used for the extraction of grid voltage phase angles, based on arctangent functions [19].…”
Section: Introductionmentioning
confidence: 99%
“…Based on the authors’ prior work [30], PID control is found to be practical through a field test on a campus microgrid system. In this study, however, the overshoot is not critical (less than 5% under a 45% heavy load pick up event).…”
Section: Microgrid Control Schemementioning
confidence: 99%
“…To maximize the restoration capability and better respond to the dynamics, based on the authors' prior work [30], DGs must share, by the same ratio, the real and reactive power output to the respective rated capacity of each DG unit. The microgrid needs to have the capability to regulate frequency and voltage to synchronize with the utility and/or other microgrids.…”
Section: Microgrid Control Schemementioning
confidence: 99%
“…In Reference 24, for a grid‐connected MG, new control and power management strategy were presented. All these methods are based on dq CCT where phase angle from the grid voltages need to be extracted accurately for Park transformation to ensure grid voltage and dq axes currents are in phase 25 . Most commonly used technique nowadays for phase angle extraction of the grid voltage or grid synchronization is phase‐locked loop (PLL) 26,27 .…”
Section: Introductionmentioning
confidence: 99%